2021
DOI: 10.1021/acsomega.1c03477
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Decorated PLGA-NPs Loaded with Tannic Acid/Vitamin E Mitigate Colon Cancer via the NF-κB/β-Cat/EMT Pathway

Abstract: Colon cancer is the second highest contributor of cancer-related deaths throughout the world. Treatment strategies with tannic acid and vitamin E are envisaged as desirable and safe owing to their robust antioxidative and anti-inflammatory potential. In the present report, these bioactives have been nanoencapsulated in poly­(d,l-lactide-co-glycolic acid) (PLGA) formulations for maintaining sustained release and ensuring enhanced bioavailability. Capping of nanoparticles (NPs) with chitosan was done for enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 82 publications
(141 reference statements)
1
6
0
Order By: Relevance
“…PLGA NPs initially showed the burst release followed by the sustained release in PBS buffer, whereas in the case of PLGA–CS NPs, the burst phase was shorter, followed by prolonged release kinetics, and, hence, it acted better (Figure ). CS grafting impaired net positive charge over negative charged PLGA NPs that improved mucoadhesive properties and sustained release of drugs as reported by a different research group in their study . In our cellular uptake study, it was confirmed that the composite NPs were easily uptaken by the A549 cell line and that might be due to the improved interaction between cell and composite NPs in comparison to NPs (Figure ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…PLGA NPs initially showed the burst release followed by the sustained release in PBS buffer, whereas in the case of PLGA–CS NPs, the burst phase was shorter, followed by prolonged release kinetics, and, hence, it acted better (Figure ). CS grafting impaired net positive charge over negative charged PLGA NPs that improved mucoadhesive properties and sustained release of drugs as reported by a different research group in their study . In our cellular uptake study, it was confirmed that the composite NPs were easily uptaken by the A549 cell line and that might be due to the improved interaction between cell and composite NPs in comparison to NPs (Figure ).…”
Section: Discussionsupporting
confidence: 83%
“…CS grafting impaired net positive charge over negative charged PLGA NPs that improved mucoadhesive properties and sustained release of drugs as reported by a different research group in their study. 31 In our cellular uptake study, it was confirmed that the composite NPs were easily uptaken by the A549 cell line and that might be due to the improved interaction between cell and composite NPs in comparison to NPs ( Figure 6 ). Hence, it may be assumed that the higher cellular uptake for protein-loaded composite NPs can be achieved by using BSA-loaded PLGA–CS NPs, where these particles also show improved sustained release of BSA.…”
Section: Discussionmentioning
confidence: 52%
“…A recent study has described the development of polymeric poly D,L‐lactic‐co‐glycolic acid (PLGA) nanostructures for the delivery of tannic acid and vitamin E. The surface modification with chitosan was performed to enhance the stability and biocompatibility of nanostructures. These drug‐loaded PLGA nanoparticles inhibited EMT and invasion of colon cancer cells via inhibiting NF‐κB signaling (Nag & Das Saha, 2021). Overall, it appears that NF‐κB is a vital signaling pathway for promoting metastasis of gastrointestinal cancers via EMT induction.…”
Section: Nf‐κb and Emt Interaction In Various Cancersmentioning
confidence: 99%
“…CS-coated nanoparticles (NPs) were used to target tumors and increase the anticancer activity. Intraperitoneally injected CS-PLGA-TA-E dramatically reduced tumor number and volume and normalized colon histology in colon cancer patients [ 13 ].…”
Section: Introductionmentioning
confidence: 99%